A ras-related small GTP-binding protein, RabE1c, regulates stomatal movements and drought stress responses by mediating the interaction with ABA receptors. (May 2021) - Chen, Donghua; He, Lilong; Lin, Minyan; Jing, Ying; Liang, Chaochao; Liu, Huiping; Gao, Jianwei; Zhang, Wei; Wang, Mei
Highlights: AtRabE1c is highly induced by drought stress and expressed abundantly in guard cells. AtRabE1c loss-of-function mutants show decreased ABA sensitivity of stomatal movements and reduced drought tolerance. PYL ABA receptors interact with AtRabE1c. Loss of function of RabE1c showed reduced accumulation of PYL4 protein. The over-expression of AtRabE1c improves drought tolerance not only in Arabidopsis but in Chinese cabbage. Abstract: Drought represents a leading constraint over crop productivity worldwide. The plant response to this stress is centered on the behavior of the cell membrane, where the transduction of abscisic acid (ABA) signaling occurs. Here, the Ras-related small GTP-binding protein RabE1c has been shown able to bind to an ABA receptor in the Arabidopsis thaliana plasma membrane, thereby positively regulating ABA signaling. RabE1c is highly induced by drought stress and expressed abundantly in guard cells. In the loss-of-function rabe1c mutant, both stomatal closure and the whole plant drought stress response showed a reduced sensitivity to ABA treatment, demonstrating that RabE1c is involved in the control over transpirative water loss through the stomata. Impairment of RabE1c's function suppressed the accumulation of the ABA receptor PYL4. The over-expression of RabE1c in A. thaliana enhanced the plants' ability to tolerate drought, and a similar phenotypic effect was achieved by constitutively expressing the gene in Chinese cabbage ( Brassica rapa ssp. pekinensis ). The leading conclusion was that RabE1c promotes the degradation of PYL4, suggesting a possible genetic strategy to engineer crop plants to better withstand drought stress.